Productivity and Utilization of Leguminous Tree Indigofera zollingeriana on Dry Land - Herdiawan, Iwan; Krisnan, Rantan (Indonesian Bulletin of Animal and Veterinary Sciences, 2014)
Indigofera is well known as tarum plant, has about 700 species, including Indigofera zollingeriana. These plants are leguminous species that have high nutrient content and production as well as tolerant to abiotic stresses. This plant originated in tropical Africa, Asia, Australia, and North and South America, then spread to arid zone of Africa and Asia. In early 1900, it was brought by Europeans colonial to Indonesia. Indigofera can grow well at altitudes between 0-2200 m above sea level, with rainfall between 600-3000 mm/year. It can be used as a fodder crop because it has high nutrient content and production. It can be harvested at the age of eight months with an average production of 2,595 kg of fresh biomass/tree, with a total production of fresh approximately 52 tons/ha. Indigofera zollingeriana has crude protein content of 27.60%; neutral detergent fiber (NDF) 43.56%; acid detergent fiber (ADF) 35.24%; calcium (Ca) 1.16%; phosphorous (P) 0.26%; in vitro-dry matter digestibility (IVDMD) 67.50%; organic matter digestibility (IVOMD) 60.32%; 0.08% tannins and 0.41% saponin. Additionally I. zollingeriana is often used as green manure, cover crop in plantation areas, fabric dyeing and therapeutic herbs. Key words: Indigofera zollingeriana, characteristics, usage, dry land